Holistic Management of Atopic Dermatitis and Bronchial Asthma - Indah Dian Shafira; Aila Karyus (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2022)
Background: Atopic dermatitis is a chronic recurrent skin inflammation characterized by itching, appearing at specific predilection sites and associated with other atopic diseases. Its prevalence in Indonesia tends to increase every year. Objective: Implementing evidence-based family medicine services for patients by identifying risk factors and clinical problems and managing patients with a patient-centered and family-focused approach. Method:This case report obtained primary data through autoanamnesis, anamnesis, physical examination, and home visits. A holistic diagnostic assessment is carried out quantitatively and qualitatively. Result: The patient is a 69-year-old female with atopic dermatitis and asthma. She thought that her skin condition would improve by scratching and applying ointment. She was worried that the itching would get worse and disturb her sleep. She hopes her skin condition can improve. Patients and families had atopic history, advanced age, lack of knowledge about the disease, and exposure to allergens. Conclusion: This patient's holistic diagnostic and comprehensive management was based on the latest theory and research. During the evaluation, there was a clinical improvement in the patient, an increase in knowledge, and a change in the patient's and family's behavior.